2018
DOI: 10.3390/ani8100184
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combined Effects of Clostridium butyricum and Saccharomyces cerevisiae on Growth Indices, Intestinal Health, and Immunity of Broilers

Abstract: Simple SummaryAfter banning the use of antibiotics as growth promoters in poultry production, scientists had to find efficient and safe alternatives. Because of their useful properties, two types of probiotic bacteria were chosen to be administrated in a broiler diet, either individually or combined. Useful effects were obtained regarding improvements of growth performance, and immunity.AbstractA total of 120 1-day-old commercial Cobb chicks were used to study the effects of Clostridium butyricum (C. butyricum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…In the present study, diets supplemented with C. butyricum or a combination of S. boulardii and P. acidilactici were examined. Diets supplemented with C. butyricum reduced ADFI and increased feed conversion, which is similar to the results in broilers in Mervat et al [32]. However, the combination of probiotics had no effect on laying performance.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, diets supplemented with C. butyricum or a combination of S. boulardii and P. acidilactici were examined. Diets supplemented with C. butyricum reduced ADFI and increased feed conversion, which is similar to the results in broilers in Mervat et al [32]. However, the combination of probiotics had no effect on laying performance.…”
Section: Discussionsupporting
confidence: 87%
“…Clostridium butyricum produces butyric acid and provides energy to the intestinal epithelium, decreases intestinal pH, and preserves the intestinal environment [ 6 ]. Research confirms that C. butyricum has beneficial effects on lipid metabolism, immune function, and culturable microbiota [ 7 , 8 ] and protects broilers from intestinal infections [ 9 ]. Gao et al (2012) reported that oral administration of C. butyricum , as a promising probiotic, promoted individual performance [ 10 ].…”
Section: Introductionmentioning
confidence: 97%
“…It can survive low pH and high bile concentrations. Clostridium butyricum seems to be a promising probiotic to provide protection against intestinal infections [11], and some reports show beneficial effects of C. butyricum strains on growth performance, lipid metabolism, immune function and culturable microbiota [12,13]. Although wheat bran and C. butyricum supplementations have been investigated from various aspects in broilers at slaughter age, little information is available on the effects of wheat bran using culture-independent methods [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%